Las historias de Salustio y los acontecimientos del año 75 a.c. en Hispania (fragmentos I 125, II 89-97M) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
It is studied the existence of an ethnographic excursus about the celtiberi in the last section of the second book. The fragments are analysed in their context in order to establish their sense, including the fragmentsof the Sallustian palimpsest. A new general scheme of the section is proposed, based on the internal information of the fragments and also on the ethnographic differences of the Hispanic peoples.
Keywords: Sallust.; Histories.; Ethnography.; Hispania.; Celtiberi.